2020
DOI: 10.1111/ans.15674
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of pre‐operative endoscopic retrograde cholangiopancreatography in diagnosis and management of forme fruste choledochal cyst in children

Abstract: BackgroundForme fruste choledochal cyst (FFCC), characterized by a minimally dilated common bile duct (CBD) and associated pancreaticobiliary maljunction (PBM), is difficult to diagnose in a timely manner in clinical practice. However, endoscopic retrograde cholangiopancreatography (ERCP) can clearly delineate CBD and PBM. Hence, we evaluated the value of ERCP in the diagnosis and management of FFCC.MethodsThe medical records of patients diagnosed with FFCC were retrospectively reviewed. From January 2003 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In infants, MRCP may not visualize healthy extrahepatic bile ducts and can lead to false positivity for the diagnosis of neonatal cholestatic diseases [10]. ERCP visualizes the biliary tree in infants with a high success rate and may avoid unnecessary surgery if biliary ▶ atresia is excluded [11,12]. In our study, 10 % of ERCP procedures were diagnostic for cases of neonatal cholestasis only.…”
Section: Discussionmentioning
confidence: 75%
“…In infants, MRCP may not visualize healthy extrahepatic bile ducts and can lead to false positivity for the diagnosis of neonatal cholestatic diseases [10]. ERCP visualizes the biliary tree in infants with a high success rate and may avoid unnecessary surgery if biliary ▶ atresia is excluded [11,12]. In our study, 10 % of ERCP procedures were diagnostic for cases of neonatal cholestasis only.…”
Section: Discussionmentioning
confidence: 75%
“…Preoperative therapeutic biliary drainage in patients with CC with persistent or exacerbated symptoms is considered to help make the surgery easier to perform and help them recover rapidly after surgery [ 28 29 ]. A previous group that underwent biliary drainage through ERCP before surgery had significantly less intraoperative blood loss and transfusion and shorter postoperative length of stay than a group that did not [ 30 ]. Younger patients are known to have higher risks for complications with ERCP [ 31 32 ]; however, recent studies have shown that the efficacy and safety of ERCP in infants and children are comparable to those in adults [ 23 33 34 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final goal of treatment is resection of the dilated common bile duct and reconstruction of the biliary system. ERCP is useful in preoperative diagnosis and management of complications 53 …”
Section: Biliary Indications For Ercp and Eusmentioning
confidence: 99%